Efectividad comparada del programa ampliado vs. programa tradicional de salud sexual y reproductiva en adolescentes de 4to año de secundaria del i.e. josé carlos mariategui del distrito el porvenir: 2010 - Mayorga Lau, Kelly Elizander (2011)
This study show the results of the experience in the application of educational programs on sexual and reproductive health in adolescent with the purpose of analyzing the efectivity of the sexual reproductive health when EsSalud prepare secondary teacher about sexual reproductive health who at the end of the course prepare to adolescents since two years, for this study is traditional program has biologist influence and risk compare with Widely program it has reflexive influence and use cooperative learning technical and took adolescents’s opinions, this program was made by investigator. The application of questionnaire to detect information for Widely program, thereinafter they were designed and applied workshops, to measure the advances in the workshops were made evaluations pre and post test to comparative the efectivity of the programs about knowledge and methology acceptation. This prospective study had a population of 78 adolescents subject to analyzing of the comparative efectivity of the two programs subject to study, the group A was the traditional program and B widely program between May until December 2010 at the I.E JOSE CARLOS MARIATEGUI of Porvenir. Results confirm predictive value about knowledge and methology acceptation of widely program with statistical significance. The results are encouraging; however, it is required to widen the coverage of the actions, to improve the elevation instruments to measure the advances and the impact of the program, to work coordinately with other institutions.